2018
DOI: 10.1007/s10461-018-2132-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Health Coaching Intervention to Enhance Retention in Care: California Collaborative Treatment Group 594

Abstract: Poor linkage, engagement and retention remain significant barriers in achieving HIV treatment goals in the US. HIV-infected persons entering or re-entering care across three Southern California academic HIV clinics, were randomized (1:1) to an Active, Linkage, Engagement, Retention and Treatment (ALERT) specialist for outreach and health coaching, or standard of care (SOC). The primary outcome of time to loss to follow up (LTFU) was compared using Cox proportional hazards regression modeling. No differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Most studies were non-RCTs (81%) [13–16,18,21,32–56]. For the eight RCTs, comparison arms were care as usual [19,57,58], wait-list control [59], featured content unrelated to re-engaging in care [60,61], or they did not receive an enhanced component that the intervention arm received [16,62].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies were non-RCTs (81%) [13–16,18,21,32–56]. For the eight RCTs, comparison arms were care as usual [19,57,58], wait-list control [59], featured content unrelated to re-engaging in care [60,61], or they did not receive an enhanced component that the intervention arm received [16,62].…”
Section: Resultsmentioning
confidence: 99%
“…To assess the effect of study design on the findings, the Q B statistics showed that the aggregated effect sizes in RCTs were significantly smaller than the ones observed in non-RCTs for retention (Q B = 10.21, P = 0.001), but not for viral suppression (Q B = 3.42, P = 0.06). We did not conduct a stratified meta-analysis for re-engagement because only one study was an RCT [58].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations